A Simple Way to Fix a Lateral Meniscal Root Tear. Issue 4 (May 2021) - Zaffagnini, Stefano; Grassi, Alberto; Dal Fabbro, Giacomo
Background: Meniscal posterior root tears, which are often associated with anterior cruciate ligament (ACL) injury, lead to the loss of normal biomechanical and kinematic behavior of menisci. Several arthroscopic techniques have been introduced to address this kind of injury. In this video, a simple all-inside technique to repair posterior lateral root tear (PLRT) is presented. Indications: To repair type 1, type 2, and type 4 PLRT. Technique: The torn lateral meniscus root is sutured to the medial fibers of the posterior cruciate ligament (PCL), with an arthroscopic all-inside repair system, with the purpose of reproducing the stabilizing function of the meniscofemoral ligaments. Results: This procedure allows restoration of the correct position of the detached horn, and restores meniscal stability with satisfactory clinical outcomes. Discussion/Conclusion: The technique described represents a simple and fast arthroscopic all-inside procedure to repair PLRT in association with concomitant procedure, such as ACL reconstruction. However, outcome reports of this technique are still lacking in the literature, and further studies are needed to confirm the authors' results. Graphical Abstract This is a visual representation of the abstract.